2001
DOI: 10.1055/s-2001-11513
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Aliphatic Acid Amides from Zanthoxylum piperitum on Isolated Gastrointestinal Tract

Abstract: beta-Sanshool and gamma-sanshool, unsaturated aliphatic acid amides isolated from the pericarpium of Zanthoxylum piperitum De Candolle (Rutaceae), relax the circular muscle of the gastric body, as well as contract the longitudinal muscle of the ileum and distal colon in an experimental system using the gastrointestinal tract isolated from a guinea pig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 0 publications
2
29
0
1
Order By: Relevance
“…Therefore, prolonged ingestion or topical application of capsaicinoids can be successful in managing painful conditions such as rheumatoid arthritis, osteoarthritis, diabetic neuropathy, postherpetic, neuralgia, postmastectomy pain syndrome, cluster headache, reflex sympathetic dystrophy and gastro-intestinal related problems like reflux and functional dyspepsia (Holzer, 2011;Philip and Thakur, 2011). On contrast, depending on the type of NAA, acute ingestion of NAAs induce gastric mobility via binding to the TRPV1 receptor (capsaicinoids), indirectly by releasing acethylcholine and other neurotransmitters or by acting directly on the smooth muscles (sanshools) (Hashimoto et al, 2001;Holzer, 2011).…”
Section: Othersmentioning
confidence: 99%
“…Therefore, prolonged ingestion or topical application of capsaicinoids can be successful in managing painful conditions such as rheumatoid arthritis, osteoarthritis, diabetic neuropathy, postherpetic, neuralgia, postmastectomy pain syndrome, cluster headache, reflex sympathetic dystrophy and gastro-intestinal related problems like reflux and functional dyspepsia (Holzer, 2011;Philip and Thakur, 2011). On contrast, depending on the type of NAA, acute ingestion of NAAs induce gastric mobility via binding to the TRPV1 receptor (capsaicinoids), indirectly by releasing acethylcholine and other neurotransmitters or by acting directly on the smooth muscles (sanshools) (Hashimoto et al, 2001;Holzer, 2011).…”
Section: Othersmentioning
confidence: 99%
“…Hydroxy b -sanshool was isolated from the extract of Zanthoxylum fruit (Rutaceae, Zanthoxylum piperitum DE CANDOLLE, pericarpium) by the method described previously (10). Dai-kenchu-to extract powder {extracts in water from a 5:3:2 mixture of dried ginger root (Zingiberaceae, Zingiber officinale ROSCOE, rhizoma), ginseng (Araliaceae, Panax ginseng C.A.…”
Section: Drugsmentioning
confidence: 99%
“…It was reported that the contractile effect is due to the release of acetylcholine and other neurotransmitters (10). Natural pungent substances, capsaicin (red pepper), piperine (black pepper) and shogaol (ginger) have contractile effects on guinea pig ileum, and these effects were induced via release of substance P from sensory nerve endings (11 -15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Große chemische Ähnlichkeit besteht mit den Amiden des Szechuanpfeffers (Zanthoxylum spec., Rutaceae) [4,60,63,98,186,201,206 Auch Alkamide der Zanthoxylum-Species aus der Familie der Rutaceae weisen teilweise Ă€hnliche bis identische Strukturen mit Acmella und anderen Vertretern der Ecliptinae (Asteraceae) auf [4,60,63,98,186,201,206]. Isobutyl-Rests stattfindet [4,122,186,187].…”
Section: Vergleich Der Pollenunclassified